Farmacoepidemiologia e o uso de medicamentos potencialmente inapropriados em idosos institucionalizados e não institucionalizados - Zanetti, D. F. S.; Queiroz, A. B. B.; Cavalcanti, P. P. (Scientific Electronic Archives, 2018)
Pharmacoepidemiology is a field of study that connects two broad areas: clinical pharmacology, which studies the effects of drugs on humans, and an epidemiology, which studies a distribution and determinants of disease in the population. This study aimed to verify the prevalence of potentially inappropriate drugs in institutionalized and non-institutionalized elderly people, both in the city of Sinop-MT, as well as to describe socio-demographic characteristics, family arrangements, drug use and comorbidities. The sample consisted of 40 elderly people, 26 from a community day center and 14 from the Long Stay Institute (LSI), thus constituting two groups. The results of the study showed that polypharmacy is high among the elderly, and among these polypharmacy Potentially Inappropriate Use Medications (PIM) were detected. With regard to the concomitant diseases, many report epigastralgia, but it is a question of being investigated, since the use of medications induces the use of more and more medications itself. In addition, the drugs are equally distributed among adults and the elderly, and there are physiological modifications in a geriatric individual that lead to drug interactions and/or adverse reactions.